Analisis Akuntabilitas dalam Pengelolaan Keuangan di Kecamatan Magelang Selatan Kota Magelang - Septiana Putri Pangestu; Ayu Alfina Wijiyanti; Muhammad Muhaiminul Azizul K; Elvira Ayu Lestari (Jurnal Akuntan Publik, 2025)
Appropriate financial management is key in managing regional finances that are vulnerable to risk. Even though financial risk exists, this does not always indicate a violation. Good financial management in the regions is the key to demonstrating the effectiveness and efficiency of the use of public funds. This study uses a qualitative approach with primary data sources through interviews and direct observation in the field. The research results show that the South Magelang District OPD has implemented accounting procedures in accordance with regulations, achieving a full level of accountability with optimal transparency in administration and financial accountability. However, continued efforts are needed in financial management, supervision and reporting to maintain public trust and increase the effectiveness of financial management in the future.